A screening tool for acquired communication disorders in Aboriginal Australians after brain injury: lessons learned from the pilot phase. Issue 11 (1st November 2020) - Armstrong, Elizabeth; McAllister, Meaghan; Hersh, Deborah; Katzenellenbogen, Judith M.; Thompson, Sandra C.; Coffin, Juli; Flicker, Leon; Woods, Deborah; Hayward, Colleen; Ciccone, Natalie
ABSTRACT: Background : Screening for communication disorders in a cross-cultural context presents numerous challenges, especially when the screening tool has been designed for use in one specific cultural and linguistic context. Translation enables it to be administered to speakers of a variety of languages, but does not account for the effects of worldview nor the linguistic and cultural context that motivated the original version. Clients assessed with tools not appropriate for their culture may be at a disadvantage in completing the assessment. Furthermore, this may influence diagnostic/screening judgements and decision-making related to access to relevant services. Aims : To describe the piloting of a screening tool developed to detect acquired communication disorders in Aboriginal Australians after stroke and traumatic brain injury – the Aboriginal Communication Assessment After Brain Injury (ACAABI). The study aims to i) assess whether a non-speech pathologist (e.g., Aboriginal Health Practitioner) can easily and accurately administer the tool, ii) determine whether the tool can identify acquired communication disorders of any type, and iii) describe a series of practical challenges encountered. Methods and procedures : Aboriginal Research Assistants (ARAs) reflected the role of the Aboriginal Health Practitioner. ARAs administered the tool to 38 Aboriginal brain injury survivors across Western Australia. A Speech Language Pathologist (SLP) observed the assessments to evaluate test administration. Another SLP undertook an independent communication assessment to provide information to an expert panel who produced a consensus diagnosis with which to compare the tool results. Sensitivity and specificity analyses were undertaken in terms of the total score and individual section scores. Field notes captured challenges encountered. Outcomes and results : Aboriginal Research Assistants could administer the tool effectively for the majority of participants, with some variations occurring. The tool appeared to be sensitive to detection of acquired communication disorders but had a high false-positive rate. However, small sample size and lack of comparative groups of non-brain-damaged individuals and those without communication disorders limits interpretation at this time. Challenges included participant recruitment, scheduling of appointments across large geographical distances, and availability of Aboriginal Research Assistants. Conclusions : The ACAABI looks promising in its ability to provide a culturally appropriate and secure way to screen for acquired communication disorders in Aboriginal people after brain injury for the purpose of referring onwards for further investigation. However, numerous challenges were encountered in the piloting and further work is needed to adjust the tool, enabling reliability, sensitivity and specificity analyses to be conclusive.